Allosteric regulation of glycerol kinase by enzyme IIIglc of the phosphotransferase system in Escherichia coli and Salmonella typhimurium. - Novotny, M J (1985)
The mechanism by which enzyme IIIglc of the bacterial phosphotransferase system regulates the activity of crystalline glycerol kinase from Escherichia coli has been studied, and the inhibitory effects have been compared with those produced by fructose-1,6-diphosphate. It was shown that the free, but not the phosphorylated, form of enzyme IIIglc inhibits the kinase. Mutants of Salmonella typhimurium were isolated which were resistant to inhibition by either enzyme IIIglc (glpKr mutants) or fructose-1,6-diphosphate (glpKi mutants), and each mutant type was shown to retain full sensitivity to inhibition by the other regulatory agent. Other mutants were fully or partially resistant to regulation by both agents. The two regulatory sites on the kinase are evidently distinct but must overlap or interact functionally. Kinetic analyses have revealed several mechanistic features of the regulatory interactions. (i) Inhibition by both allosteric regulatory agents is strongly pH dependent, with maximal inhibition occurring at ca. pH 6.5 under the assay conditions employed. (ii) Binding of enzyme IIIglc to glycerol kinase is also pH dependent, the Ki being near 4 microM at pH 6.0 but near 10 microM at pH 7.0. (iii) Whereas fructose-1,6-diphosphate inhibition apparently requires that the enzyme exist in a tetrameric state, both the dimer and the tetramer appear to be fully sensitive to enzyme IIIglc inhibition. (iv) Inhibition by enzyme IIIglc (like that by fructose-1,6-diphosphate) is noncompetitive with respect to both substrates. (v) The inhibitory responses of glycerol kinase to fructose-1, 6-diphosphate and enzyme IIIglc show features characteristic of positive cooperativity at low inhibitor concentration. (vi) Neither agent inhibits completely at high inhibitor concentration. (vii) Apparent negative cooperativity with respect to ATP binding is observed with purified E. coli glycerol kinase, with glycerol kinase in crude extracts of wild-type S. typhimurium cells, and with glpKr and glpKi mutant forms of glycerol kinase from S. typhimurium. These results serve to characterize the regulatory interactions which control the activity of glycerol kinase by fructose-1,6-diphosphate and by enzyme IIIglc of the phosphotransferase system.